Analysis of the Spectrum Pattern of Human Blood Plasma Using Raman Spectroscopy - Rahmasari, Anak Agung Intan; Suryatika, Ida Bagus Made; Supardi, I Wayan (BULETIN FISIKA, 2024)
A research has been carried out on the analysis of the spectrum pattern of human blood plasma using Raman spectroscopy. The research was conducted at the Forensic, Science and Criminology Laboratory. Blood plasma samples were obtained from blood donors at the Indonesian Red Cross Blood Donor Unit, Sanglah Central General Hospital, Denpasar. This study aims to determine the spectrum pattern and obtain typical values ??of the wavenumber and intensity of human blood plasma. The method used is direct irradiation of blood samples with Raman spectroscopy using a power level of 400 mW and an exposure time of 3000 ms. The results showed that blood types A and B had one distinctive peak at wavenumber of 279.365 cm -1 , blood types O and AB had three distinctive peaks, e.g. at wavenumbers 219.114, 259.375, and 279.365 cm -1 . The maximum intensity value of the four different blood groups, namely blood type A is 1017.456 a.u, blood group B is 1006.857 a.u, blood group O are 664.468 a.u, 666.840 a.u, 667.943 a.u, and AB blood group are 670.791 a.u, 671.670 a.u, and 669.710 a.u.